2021
DOI: 10.3390/antibiotics10081012
|View full text |Cite
|
Sign up to set email alerts
|

The Revival of Aztreonam in Combination with Avibactam against Metallo-β-Lactamase-Producing Gram-Negatives: A Systematic Review of In Vitro Studies and Clinical Cases

Abstract: Infections caused by metallo-β-lactamase (MBL)-producing Enterobacterales and Pseudomonas are increasingly reported worldwide and are usually associated with high mortality rates (>30%). Neither standard therapy nor consensus for the management of these infections exist. Aztreonam, an old β-lactam antibiotic, is not hydrolyzed by MBLs. However, since many MBL-producing strains co-produce enzymes that could hydrolyze aztreonam (e.g., AmpC, ESBL), a robust β-lactamase inhibitor such as avibactam could be give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 84 publications
0
73
0
4
Order By: Relevance
“…Pending the development of new molecules, combinations of ATM with different BLIs are being investigated for the treatment of infections sustained by Enterobacterales expressing both serine-ß-lactamases and MBLs [ 22 , 23 ]. The combination of ATM with AVI was one of the most promising and has also been used in clinical settings with relatively good results [ 7 ]. Our data showed that, against MBL-producers, DBO derivatives were the most active BLIs when combined with ATM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pending the development of new molecules, combinations of ATM with different BLIs are being investigated for the treatment of infections sustained by Enterobacterales expressing both serine-ß-lactamases and MBLs [ 22 , 23 ]. The combination of ATM with AVI was one of the most promising and has also been used in clinical settings with relatively good results [ 7 ]. Our data showed that, against MBL-producers, DBO derivatives were the most active BLIs when combined with ATM.…”
Section: Discussionmentioning
confidence: 99%
“…The only β-lactam effective, because it is not hydrolyzed, against MBL-producers is ATM, a monobactam approved in 1986 but currently infrequently used due to the spread of extended-spectrum β-lactamases (ESBLs) [ 7 ]. ATM is effective against MBL-producer infections as long as these isolates are ESBL-negative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, CZA is active against Ambler A, C and D beta-lactamases including extended spectrum beta-lactamases such as CTX-M, AmpC and OXA-48. In a systematic review of in vitro data, MIC values ≤ 4 mg/L for ATM in combination with CZA have been described in 79.6% of the MBL-producing Enterobacterales [ 26 ].…”
Section: Available Drugsmentioning
confidence: 99%
“…The association was tested as a last-resort therapy and reported in a growing number of case-reports and cohorts [ 26 ]. In a multicenter cohort of 102 patients with BSI due to MBL-producing Enterobacterales (NDM n = 82, VIM n = 20), Falcone et al compared the activity of CZA/ATM with other various combination therapies [ 27 ].…”
Section: Available Drugsmentioning
confidence: 99%